ASPIRING AND INSPIRING WOMEN IN EDUCATION: KEPEMIMPINAN PEREMPUAN DAN PEMBERDAYAAN KOMUNITAS SEKOLAH DASAR DI KOTA BANJARMASIN - Suriansyah, Ahmad; Amelia, Rizky; Revia Rafianti, Wahdah; Ngadimun, Ngadimun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Women’s leadership in education plays a crucial role in fostering inclusive, participatory, and sustainable school environments, particularly at the primary school level where relational and community-based approaches are essential. This study aims to explore how female principals in primary schools in Banjarmasin City exercise leadership in empowering school communities, identify the values, strategies, and approaches they employ, and examine the challenges and opportunities they encounter in their leadership practices. Employing a qualitative research design, this study collected data through in-depth interviews, observations, and document analysis involving two female principals from public primary schools in Banjarmasin. The findings reveal that female principals demonstrate empathetic, collaborative, and transformational leadership grounded in local socio-cultural values such as religiosity and kinship. Their leadership practices emphasize participatory decision-making, inclusive learning environments, and strong partnerships with teachers, parents, and the wider community. Despite facing structural and cultural challenges, including gender bias and role duality, the principals responded strategically by strengthening professional competence, fostering trust-based relationships, and utilizing community networks as sources of support. This study concludes that women’s leadership contributes significantly to empowering school communities and shaping positive school cultures. The findings highlight the importance of systemic support and leadership development programs to strengthen women’s leadership in primary education.